Improving kindergarten students' reading ability using fantasy shadow puppet - Khoiriyah; Aulya Nanda Prafitasari; Lutfia Fitri Khatimah; Ratna Hartini (Journal of Early Childhood Care and Education, 2023)
This Classroom Action Research aims to improve students’ low reading skills. Improving reading skills will promote brain development and imagination, develop language and emotions, and strengthen relationships. Through Fantasy Shadow Puppet, students will be more interested and motivated to learn to read. To obtain the desired research results, a quantitative approach with two cycles was used. Each of the cycles covered four competencies, namely planning, action, observation, and reflection. Data was obtained by observing 20 students of Group B at TKM NU 262 AL KAMAL SIDOARJO using observation sheets. The results of the study showed a very significant increase in the students' reading ability up to 37.63% after learning using Fantasy Shadow Puppets. With Fantasy Shadow Puppets students can ask questions, guess which, then find answers (language development reactions) to the storylines they hear, the span of attention to stories becomes longer because students concentrate on stories, and are able to organize their own abilities because children learn from amazing experiences so that they will build confidence in what is conveyed.